Determinants of geographic range size in plants. Issue 3 (13th February 2020) - Sheth, Seema Nayan; Morueta‐Holme, Naia; Angert, Amy L.
Summary: Geographic range size has long fascinated ecologists and evolutionary biologists, yet our understanding of the factors that cause variation in range size among species and across space remains limited. Not only does geographic range size inform decisions about the conservation and management of rare and nonindigenous species due to its relationship with extinction risk, rarity, and invasiveness, but it also provides insights into fundamental processes such as dispersal and adaptation. There are several features unique to plants (e.g. polyploidy, mating system, sessile habit) that may lead to distinct mechanisms explaining variation in range size. Here, we highlight key studies testing intrinsic and extrinsic hypotheses about geographic range size under contrasting scenarios where species' ranges are static or change over time. We then present results from a meta‐analysis of the relative importance of commonly hypothesized determinants of range size in plants. We show that our ability to infer the relative importance of these determinants is limited, particularly for dispersal ability, mating system, ploidy, and environmental heterogeneity. We highlight avenues for future research that merge approaches from macroecology and evolutionary ecology to better understand how adaptation and dispersal interact to facilitate niche evolution and range expansion.